Pengaruh Kehamilan Usia Remaja terhadap Kejadian Anemia dan KEK pada Ibu Hamil - Irbah Nabila (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background : Adolescent pregnancy is a pregnancy that occurs at the age of 15-19 years old. Adolescent Pregnancy causes many complications, such as anemia and chronic energy deficiency. Objective : To find out more about the effect of adolescent pregnancy on the incidence of anemia and KEK in pregnant women. Methods : Using literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results : adolescence pregnancy causing anemia and KEK because of the ahe is still in its infancy which requires sufficient energy and high use of iron in the body. Conclusion : there is an influence of teenage pregnancy of the incidence of anemia and KEK in pregnant women